Evolution of humanoid robot and contribution of various countries in advancing the research and development of the platform - Akhtaruzzaman, Md.; Shafie, Amir Akramin (2010)
A human like autonomous robot which is capable to adapt itself with the changing of its environment and continue to reach its goal is considered as Humanoid Robot. These characteristics differs the Android from the other kind of robots. In recent years there has been much progress in the development of Humanoid and still there are a lot of scopes in this field. A number of research groups are interested in this area and trying to design and develop a various platforms of Humanoid based on mechanical and biological concept. Many researchers focus on the designing of lower torso to make the Robot navigating as like as a normal human being do. Designing the lower torso which includes west, hip, knee, ankle and toe, is the more complex and more challenging task. Upper torso design is another complex but interesting task that includes the design of arms and neck. Analysis of walking gait, optimal control of multiple motors or other actuators, controlling the Degree of Freedom (DOF), adaptability control and intelligence are also the challenging tasks to make a Humanoid to behave like a human. Basically research on this field combines a variety of disciplines which make it more thought-provoking area in Mechatronics Engineering. In this paper a various platforms for Humanoid Robot development are identified and described based on the evolutionary research on robotics. The paper also depicts a virtual map of humanoid platform development from the ancient time to present time. It is very important and effective to analyze the development phases of androids because of its Business, Educational and Research value. Basic comparisons between the different designs of Humanoid Structures are also analyzed in this paper. ©ICROS.